Surface structure of sodium chloride solution - Nguyen, C.; Phan, Chi; Nakahara, H.; Shibata, O. (Elsevier, 2017)
The arrangement of Na + /Cl - near the water surface was studied by simulation. The simulating result was combined with experimental surface charge to describe ionic arrangement. It was found that the interface is positively charged due to the interaction between ions and water surface molecules. The charge increased with increasing concentration. The simulations were validated with experimental measurement. The positive charge at the surface is balanced by the distribution on the diffuse zone, which is governed by the well-established Poisson-Boltzmann formulation. The “diffuse plane” was quantitatively verified by the water dipole distribution in molecular simulation. The results provide a consistent image of ionic distribution around the interfacial zone. In addition to NaCl solutions, the result also provides important basis to study other electrolyte surface.